Sustainable Supply Chain of Automobile Sector: A Literature Review - Ajay Serohi (International Journal of Supply Chain Management, 2020)
Currently, the British automotive industry still has its own benefits within economic situations. As an instance, its automotive infrastructure field is still driving the world. In the case of automotive innovation and framework, the UK also has the ability to drive and collect. According to data from the “European Automobile Association and the British Automobile Manufacturers and Traders Association”, the production of British cars in 2012 was 1.58 million, an increase of 7.7% compared to 2011, while automobile production has maintained steady growth. In 2012, 2.5 million units were supplied. During the same period, German car production declined by 8.1 percent and Spain by 16.6 percent. France lost another 12.3 percent. By 2013, the annual offer for British cars reached 1.6 million units, which has returned to levels well before the financial crisis. The overall development from the Supply Chain to the Extended Supply Chain has been carried out by various enterprises for some time. As one of the largest and dominant organisations in the world, the automotive industry can greatly influence the development of a better society. Although another combination has emerged in the field of original supply chain management, no reviewing department can fully cover the front-line research of the automotive industry. To fill this gap, this research considers the sustainable management of supply chain in the automotive industry, which was adopted around 1995 and 2017. Therefore, the research has performed a persuasive bias analysis and studied the material and their contents. According to the “Icam DEFinition for Function Modeling (IDEF0)”, content analysis is categorised according to several key business structures, which is a common way of separating business structures. The survey provides useful principles for building the automotive supply chain of the surveyor and combines robustly-distributed research theft clauses and recommendations for future investigations.Keywords: sustainable SCM, Automotive Industry, Green SCM, Electric Vehicles